FUNCTION ORIENTED HISTORY REPRESENTATION IN DATABASES - Kovács, László; Vassilakis, Costas (Computing and Informatics, 2012)
In the past years the management of temporal data has attracted numerous researchers resulting to a large number of temporal data extensions to the relational and object oriented data models. In this paper, the proposed temporal data model focuses on the functional characteristics of the histories. The paper introduces a set oriented description of the calendars together with a function oriented history concept with a history-algebra. The completeness of the proposed model with respect to the reduced temporal algebra TA is also proven. The expressive power of the proposed model is demonstrated in the end of the paper by a hospital example.